Sistema de ignição com pré-câmara operando com mistura homogênea em um motor de ignição por centelha - Giselle Elias Couto (2017)
The fleet of land vehicles currently exceeds eighty million vehicles, having grown in the last ten years more than twice the average global growth. Environmental and energy security issues are concerns about this excessive increase, as land vehicles are a major contributor to global air pollution, and confirmed oil reserves are sufficient to meet just over 52.5 years of global use. In this context, the use of a pre-chamber ignition system to burn poor blends appears as a promising strategy, as it works with less fuel and allows for lower emissions of pollutants. The present work analyzes the behavior of an engine prototype equipped with an ignition system with pre-chamber, operating with homogeneous mixture of gasoline. The performance of some engine operating parameters, such as the exhaust gas temperature, the specific fuel consumption, the fuel consumption and the fuel consumption were evaluated by means of tests performed on a bench dynamometer and evaluation of the pressure curve inside the cylinder. Efficiency of fuel conversion, thermal cycle efficiency, coefficient of variation of indicated effective mean pressure, apparent heat release rate, flame development angle and total combustion time. The analysis of these parameters allowed to evaluate the performance of the engine and to quantify the possible gains obtained when using the pre-chamber ignition system. The prototype with pre-chamber presented good performance working with stoichiometric mixture, when compared to the original engine, obtaining reductions of the specific consumption of fuel in all the range of speeds and load analyzed. When working with impoverishment of the mixture, the prototype made possible reductions in the specific fuel consumption and the peak of the combustion temperature of up to 14% and 7%, respectively, for the rotation evaluated. The prototype allowed the development of a stable combustion of the mixture for y = 1,1, with coefficients of variation of the IMEP lower than 2% for the points tested. It is concluded that the ignition system with pre-chamber, even without stratification of the mixture, shows a promising potential for the reduction of fuel consumption with good combustion stability when compared to the conventional ignition engine.